Dietary adequacy of migrated north east region college students residing in pune city, maharashtra - V. YEPTHOMI; D. GOKHALE (International Journal of Pharma and Bio Sciences, 2017)
Migration from home leads to unhealthy eating habits and consequently changes in the dietary pattern and dietary adequacy. The purpose of this study was to assess the nutritional status, pre and post migration and dietary adequacy of the participants migrated from Northeast region currently residing in Pune, Maharashtra. A total 100 college going students (18 to 25 years) across 3 universities in Pune, within 3 ethnic groups of NER using purposive sampling technique were recruited. Data was collected through interview method. The level of significance was set at p value <0.05 for all analysis. Significant associations were found between access to red meat a staple food and length of stay in Pune. Statistical significant difference for consumption of nutrients pre and post migration across genders and difference for consumption of micronutrients across three ethnic groups was observed. This baseline study on the migrated students showed change in the dietary adequacy.